Synthesis, cytostatic, antimicrobial, and anti-HCV activity of 6-substituted 7-(het)aryl-7-deazapurine ribonucleosides - Nauš, Petr; Caletková, Olga; Konečný, Petr; Džubák, Petr; Bogdanová, Kateřina; Kolář, Milan; Vrbková, Jana; Slavětínská, Lenka; Tloušt'ová, Eva; Perlíková, Pavla; Hajdúch, Marián; Hocek, Michal (Journal of medicinal chemistry, 2014)
A series of 80 7-(het)aryl- and 7-ethynyl-7-deazapurine ribonucleosides bearing a methoxy, methylsulfanyl, methylamino, dimethylamino, methyl, or oxo group at position 6, or 2,6-disubstituted derivatives bearing a methyl or amino group at position 2, were prepared, and the biological activity of the compounds was studied and compared with that of the parent 7-(het)aryl-7-deazaadenosine series. Several of the compounds, in particular 6-substituted 7-deazapurine derivatives bearing a furyl or ethynyl group at position 7, were significantly cytotoxic at low nanomolar concentrations whereas most were much less potent or inactive. Promising activity was observed with some compounds against Mycobacterium bovis and also against hepatitis C virus in a replicon assay.
Keywords: Virus Replication; Ribonucleosides; nádorové buněčné linie; Cell Line, Tumor; cytostatické látky; lidé; Humans; purinové nukleosidy; Anti-Bacterial Agents; Cytotoxins; ribonukleosidy; Cytostatic Agents; Hepacivirus; antituberkulotika; replikace viru; Antiviral Agents; antivirové látky; Antitubercular Agents; Purine Nucleosides; Mycobacterium bovis; cytotoxiny; vztahy mezi strukturou a aktivitou; antibakteriální látky; Structure-Activity Relationship